1996
DOI: 10.1002/(sici)1097-4636(199607)31:3<355::aid-jbm9>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of submicron polyethylene wear debris from synovial-fluid samples of revised knee replacements using a light-scattering technique

Abstract: The objectives of this study were to determine whether submicron-sized ultra-high-molecular-weight polyethylene (UHMWPE) wear debris was present in synovial fluid surrounding knee implants, and to report on the utility of a light-scattering technique for the in situ analysis of submicron-sized wear debris. The measured light-scattering coefficients of the implant synovial fluid samples were significantly larger than the coefficients of the control samples (p < 0.0001). The enhanced light scattering was attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…SEM analysis of the simulator fl uids revealed that PEEK implant debris particles were generally granular with an AR between 1.3 and 1.8, indicat ing that they were not exceptionally elongated and were generally more round than particles of total hip and knee implants, which generally have an AR greater than 2.0. [23][24][25][26][27][28] As a consequence of device wear in the lumbar spine, common infl ammatory mediators, such as IL-1, IL-6, and TNF-α, along with osteolysis, gross metallosis, and mass lesions, have been observed after total disc replacement, 32-38,40-42 subsequently leading to device revision. However, the importance and frequency of these fi ndings, although limited, remain unclear given the insuffi cient amount of clinical data available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SEM analysis of the simulator fl uids revealed that PEEK implant debris particles were generally granular with an AR between 1.3 and 1.8, indicat ing that they were not exceptionally elongated and were generally more round than particles of total hip and knee implants, which generally have an AR greater than 2.0. [23][24][25][26][27][28] As a consequence of device wear in the lumbar spine, common infl ammatory mediators, such as IL-1, IL-6, and TNF-α, along with osteolysis, gross metallosis, and mass lesions, have been observed after total disc replacement, 32-38,40-42 subsequently leading to device revision. However, the importance and frequency of these fi ndings, although limited, remain unclear given the insuffi cient amount of clinical data available.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the technique of light scattering has been successfully used to help quantify the total size distribution of wear particulate from both ex vivo and in vivo origins. [25][26][27] The light scattering technique, specifi cally low angle laser light scattering (LALLS), allows for the entire wear debris sample to be analyzed nondestructively while in suspension (i.e., millions to billions of particles). 26 As the LALLS method is nondestructive, it can be further augmented by direct SEM observation.…”
mentioning
confidence: 99%
“…Thus, an additional light-scattering analysis (Mastersizer 2000, Malvern, PA) was conducted. Hahn et al [9] reported the utility of a light-scattering technique for in situ analysis of submicron size wear debris in syiiovial fluid samples. They indicated that the lightscattering technique yielded particle sizes in excellent agreement with SEM-determined particle sizes, despite deviations from true sphericity.…”
Section: I039mentioning
confidence: 99%
“…The clinical triad of effusion, pain, and progressive change in the coronal alignment of the knee (most commonly into varus alignment) is characteristic of accelerated polyethylene wear 131 . The joint fluid is laden with polyethylene particles of various sizes, and aspiration can confirm the diagnosis of polyethylene-induced synovitis 23,88 . Arthroscopy can be helpful in assessing the degree of polyethylene wear and the damage of the femoral component as well as in planning a revision operation.…”
Section: Studies Of Wear In Vivomentioning
confidence: 99%